Propuesta de distribucion en planta para optimizar las condiciones productivas de la empresa Guido Tapiceria en la ciudad de Santa Marta - Granados Mercado, José Alejandro; González Palacio, Sergio David (Universidad Antonio Nariño, 2023)
Due to the inadequate design of the plant, there is a lot of improper handling of materials by workers increasing the cost of production, the plant lacks sufficient space and waste is kept anywhere and in the workstations, due to the products in process and finished products located anywhere in the process gives bad appearance to the plant, also the working conditions of workers are not adequate as they are performing their duties without proper training and skills development, there is no departmentalization or demarcation of established work areas. In our project we seek to make a plant distribution proposal that allows optimizing the arrangement of equipment, material flows and work areas in the company "Guido Tapicería" at an optimal cost, in addition, through our objectives we obtained an improvement of 19% that allows the company to stand out in the labor and competitive field.